LANGUAGE AND CULTURE: THEIR INTERRELATIONSHIP - Bekchanova Mahliyoxon Hamidjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Language and culture are inseparable components of human society that influence and shape one another. Language functions not only as a means of communication but also as a carrier of cultural values, traditions, beliefs, and social norms. Through language, individuals express their identities, preserve cultural heritage, and transmit knowledge across generations. At the same time, cultural environments influence the structure, meaning, and use of language. In the era of globalization, understanding the relationship between language and culture has become increasingly important for effective communication, language education, and intercultural cooperation. This article examines the interrelationship between language and culture, highlighting their mutual influence on communication, identity formation, education, and social development. Furthermore, the study emphasizes the significance of cultural awareness in foreign language learning and intercultural communication in the modern world.